Variable number tandem repeats of a 9-base insertion in the N-terminal domain of severe acute respiratory syndrome coronavirus 2 spike gene - Akaishi, Tetsuya; Fujiwara, Kei; Ishii, Tadashi (Frontiers in Microbiology, 2023)
The world is still struggling against the pandemic of coronavirus disease 2019 (COVID-19), caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), in 2022. The pandemic has been facilitated by the intermittent emergence of variant strains, which has been explained and classified mainly by the patterns of point mutations of the spike (S) gene. However, the profiles of insertions/deletions (indels) in SARS-CoV-2 genomes during the pandemic remain largely unevaluated yet. In this study, we first screened for the genome regions of polymorphic indel sites by performing multiple sequence alignment; then, NCBI BLAST search and GISAID database search were performed to comprehensively investigate the indel profiles at the polymorphic indel hotspot and elucidate the emergence and spread of the indels in time and geographical distribution. As a result, a polymorphic indel hotspot was identified in the N-terminal domain of the S gene at approximately 22,200 nucleotide position, corresponding to 210–215 amino acid positions of SARS-CoV-2 S protein. This polymorphic hotspot was comprised of adjacent 3-base deletion (5’-ATT-3’; Spike_N211del) and 9-base insertion (5’-AGCCAGAAG-3’; Spike_ins214EPE). By performing NCBI BLAST search and GISAID database search, we identified several types of tandem repeats of the 9-base insertion, creating an 18-base insertion (Spike_ins214EPEEPE, Spike_ins214EPDEPE). The results of the searches suggested that the two-cycle tandem repeats of the 9-base insertion were created in November 2021 in Central Europe, whereas the emergence of the original one-cycle 9-base insertion (Spike_ins214EPE) would date back to the middle of 2020 and was away from the Central Europe. The identified 18-base insertions based on 2-cycle tandem repeat of the 9-base insertion were collected between November 2021 and April 2022, suggesting that these mutations could not survive and have been already eliminated. The GISAID database search implied that this polymorphic indel hotspot to be with one of the highest tolerability for incorporating indels in SARS-CoV-2 S gene. In summary, the present study identified a variable number of tandem repeat of 9-base insertion in the N-terminal domain of SARS-CoV-2 S gene, and the repeat could have occurred at different time from the insertion of the original 9-base insertion.